1969
DOI: 10.1099/0022-1317-4-4-557
|View full text |Cite
|
Sign up to set email alerts
|

The Attenuation, with Loss of Oncogenicity, of the Herpes-type Virus of Marek's Disease (Strain hprs-16) on Passage in Cell Culture

Abstract: SUMMARYThe herpes-type virus of Marek's disease showed a gradual increase in the rate of development of cytopathic effect on passage in cell culture. By the 6oth passage macroscopic plaques were produced after 6 days under fluid overlay, but no cell-free virus could be recovered after filtration of culture medium.A loss of pathogenicity for chicks was noticed in the virus after 33 passages in cell culture. Furthermore, an antigenic change occurred between the 2oth and 3oth passage which was characterized by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0
1

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(105 citation statements)
references
References 6 publications
5
99
0
1
Order By: Relevance
“…The virus strains used were as follows: HPRS 16 (Purchase & Biggs, 1967), HPRS 16/att (Churchill et al, 1969), HVT strain FC126 (Witter et al, 1970) and HPRS 24 (Biggs & Milne, 1972). All virus strains were propagated in chick embryo fibroblasts (CEF) as cell-associated virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus strains used were as follows: HPRS 16 (Purchase & Biggs, 1967), HPRS 16/att (Churchill et al, 1969), HVT strain FC126 (Witter et al, 1970) and HPRS 24 (Biggs & Milne, 1972). All virus strains were propagated in chick embryo fibroblasts (CEF) as cell-associated virus.…”
Section: Discussionmentioning
confidence: 99%
“…Hirai et al (1981) have recently reported a change in restriction endonuclease patterns of the serotype 1 strains GA and JM during attenuation. The purpose of this study was to compare the patterns obtained with HPRS 16, HPRS 16/att and HPRS 24 and in particular to study the homology between these strains, since little is known about the genetic relatedness of serotypes 1 and 2.The virus strains used were as follows: HPRS 16 (Purchase & Biggs, 1967), HPRS 16/att (Churchill et al, 1969), HVT strain FC126 (Witter et al, 1970) and HPRS 24 (Biggs & Milne, 1972). All virus strains were propagated in chick embryo fibroblasts (CEF) as cell-associated virus.…”
mentioning
confidence: 99%
“…Serum antibodies against MDV are conventionally detected by immunodiffusion or an indirect immunofluorescence assay (Sharma, 1980). For both assays, a low passage number MDV stock and a rather cumbersome procedure are necessary to prepare the antigen because the A Ag disappears from infected cells after serial passage in vitro (Churchill et al, 1969;Ikuta et al, 1983) and the antigens are produced at low levels by infected cells. The high expression of the recombinant A Ag by recombinant AcNPV, in combination with ELISA, may provide a more efficient method for the detection of antibodies to MDV.…”
Section: Immunogenicity Of the Recombinant A Agmentioning
confidence: 99%
“…Moreover, the localization in the genomes of pathogenic and non-pathogenic viruses of the genes that encode A Ags, and their complete nucleotide sequences, have been reported (Isfort et al, 1986(Isfort et al, , 1987Coussens & Velicer, 1988;Binns & Ross, 1989). The A Ag of pathogenic viruses has been reported to be lost during attenuation of the virus by serial passage in culture (Churchill et al, 1969;Ikuta et aL, 1983), but the role of the A Ag in the course of infection and in the production of protective immunity against MD has not been studied widely. One of the problems in examining the role of the antigen is the difficulty in obtaining the antigenic protein in sufficient quantity in an authentic form, free from contamination with other viral antigens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation